Colorectal cancer Prospective study. Preliminary analysis - Sarroca, Carlos; Leites, Alejandro; Denis, María; Farcic, Antonio; Della Valle, Adriana; di Giovani, Luján (Cirugía del Uruguay, 1995)
The Coloproctology Section at the HCFFAA (Army Central Hospital) has been attracting carriers of colorrectal cancer by means of a computer protocol follow-up. The main epidemiological, diagnostica/ and therapeutical variables are described. 145 patients with colorrectal cancer were recruited between 1984 and 1993, with a mean age of 63, 7 years and a mate frequency of 86/145 (59%).